Human epidermal growth factor receptor 2 positive (HER2+) metastatic breast cancer: how the latest results are improving therapeutic options - Hanfang Jiang; Hope S. Rugo (Therapeutic Advances in Medical Oncology, 2015)
Human epidermal growth factor receptor 2 positive (HER2+) metastatic breast cancer (MBC) remains an incurable disease, and approximately 25% of patients with HER2+ early breast cancer still relapse after adjuvant trastuzumab-based treatment. HER2 is a validated therapeutic target that remains relevant throughout the disease process. Recently, a number of novel HER2 targeted agents have become available, including lapatinib (a small molecule tyrosine kinase inhibitor of both HER2 and the epidermal growth factor receptor), pertuzumab (a new anti-HER2 monoclonal antibody) and ado-trastuzumab emtansine (T-DM1, a novel antibody–drug conjugate), which provide additional treatment options for patients with HER2+ MBC. The latest clinical trials have demonstrated improved outcome with treatment including pertuzumab or T-DM1 compared with standard HER2 targeted therapy. Here we review the clinical development of approved and investigational targeted agents for the treatment of HER2+ MBC, summarize the latest results of important clinical trials supporting use of these agents in the treatment of HER2+ MBC, and discuss how these results impact therapeutic options in clinical practice.